Leadership development practices as drivers of employee attitudes. Issue 2 (14th March 2016) - Khoreva, Violetta
Abstract : Purpose: – The purpose of this paper is to examine the association between leadership development practices and the following employee attitudes: affective commitment, commitment to acceptance of increasing performance demands and commitment to building competencies. Building on social exchange theory, the study seeks to reveal whether affective commitment mediates the relationship between leadership development practices and both commitment to acceptance of increasing performance demands and commitment to building competencies. Design/methodology/approach: – Structural equation modelling was utilized to analyse survey data representing a sample of 332 high-potential employees in eight Nordic multinational corporations. Findings: – The study findings show that by means of affective commitment, organizations can expect an induced commitment to acceptance of increasing performance demands as well as an induced commitment to building relevant competencies among employees who engage in leadership development practices. Research limitations/implications: – Given the cross-sectional nature of the study, future research is encouraged to look into how the relationship between leadership development practices and employee attitudes evolves over time. Originality/value: – The study provides insights into the underlying processes by which leadership development practices become reflected in desired employee attitudes. It offers a useful point for future efforts to explore the impact of human resource management (HRM) on employees and organizations through various mediators with the purpose of establishing the current trends within HRM and avoiding tensions in future.